Snakehead vesiculovirus (SHVV) infection alters striped snakehead (Ophicephalus striatus) cells (SSN-1) glutamine metabolism and apoptosis pathways. Issue 102 (July 2020) - Sun, Lindan; Sarath Babu, V; Qin, Zhendong; Su, Youlu; Liu, Chun; Shi, Fei; Zhao, Lijuan; Li, Jun; Chen, Keping; Lin, Li
Abstract: Snakehead vesiculovirus (SHVV) causes enormous economic losses in snakehead fish ( Ophicephalus striatus) culture. Understanding replication mechanisms of virus is considerable significance in preventing and treating viral disease. In our previous studies, we have reported that glutamine starvation could significant inhibit the replication of SHVV. Furthermore, we also showed that SHVV infection could cause apoptosis of striped snakehead fish cells (SSN-1). However, the underlying mechanisms remain enigmatic. To decipher the relationships among the viral infection, glutamine starvation and apoptosis, SSN-1 cells transcriptomic profilings of SSN-1 cells infected with or without SHVV under glutamine deprived condition were analyzed. RNA-seq was used to identify differentially expressed genes (DEGs). Our data revealed that 1215 up-regulated and 226 down-regulated genes at 24 h post-infection were involved in MAPK, apoptosis, RIG-1-like and toll-like receptors pathways and glutamine metabolism. Subsequently, DEGs of glutamine metabolism and apoptosis pathways were selected to validate the sequencing data by quantitative real-time PCR (qRT-PCR). The expression patterns of both transcriptomic data and qRT-PCR were consistent. We observed that lack of glutamine alone could cause mild cellular apoptosis. However, lack of glutamine together with SHVV infection could synergistically enhance cellular apoptosis. When the cells were cultured in complete medium with glutamine, overexpression of glutaminase (GLS), an essential enzyme for glutamine metabolism, could significantly enhance the SHVV replication. While, SHVV replication was decreased in cells when GLS was knocked down by specific siRNA, indicating that glutamine metabolism was essential for viral replication. Furthermore, the expression level of caspase-3 and Bax was significantly decreased in SHVV infected cells with GLS overexpression. By contrast, they were significantly increased in SHVV infected cells with GLS silence by SiRNA, indicating that SHVV infection activated the Bax and caspase-3 pathways to induce apoptosis independent of glutamine. Our results reveal that SHVV replication and starvation of glutamine could synergistically promote the cellular apoptosis, which will pave a new way for developing strategies against the vial infection. Highlights: Transcriptomic data of cells infected by SHVV with glutamine deprivation was analyzed. Lack of glutamine and SHVV infection enhanced cellular apoptosis synergistically. SHVV infection activated the Bax and caspase-3 pathways independent of glutamine.